A New Estimate of Transaction Costs - Lesmond, David A.; Ogden, Joseph P.; Trzcinka, Charles A. (Review of Financial Studies, 1999)
Transaction costs are important for a host of empirical analyses from market efficiency to international market research. But transaction costs estimates are not always available, or where available, are cumbersome to use and expensive to purchase. We present a model that requires only the time series of daily security returns to endogenously estimate the effective transaction costs for any firm, exchange, or time period. The feature of the data that allows for the estimation of transaction costs is the incidence of zero returns. Incorporating zero returns in the return-generating process, the model provides continuous estimates of average round-trip transaction costs from 1963 to 1990 that are 1.2% and 10.3% for large and small decile firms, respectively. These estimates are highly correlated (85%), with the most commonly used transaction cost estimators.